Introduction: Indentured bodies/embodiments of indenture - Sinah Theres Kloß; Jennifer Leetsch (Journal of Indentureship and its Legacies)
Indentureship had profound and lasting effects on the bodies of those involved. Recruitment processes, along with the harrowing conditions of transport and labour, radically reshaped the material and physical realities of indentured labourers, influencing not only their immediate bodily experiences but also the socio-cultural practices and embodied memories they would pass down to future generations. As such, indentured corporeality dwells in but also extends beyond the tangible realm of labour, touching on deeper questions of how bodies can be understood, experienced and mediated under colonial exploitation and beyond. To trace the intricate interplay between the concrete and sensory actualities of indentured bodies and the cultural processes inherent to embodiments of indenture , this special issue brings together interdisciplinary perspectives that examine how bodies became both sites of colonial inscription and sites of resilience and resistance. Through historical analysis, literary exploration, artistic representation and anthropological insight, contributors attend to how the afterlives of indenture continue to shape our understanding of indentured identity, memory and belonging, revealing the body as both a marker of oppression and a medium for enduring cultural expression.